2001
DOI: 10.1051/lait:2001144
|View full text |Cite
|
Sign up to set email alerts
|

Aptitude du lait de chèvre à l'acidification par les ferments lactiques - Facteurs de variation liés à la composition du lait

Abstract: -Compositional factors involved in the variable acidification capacity of goat milk by lactic starters. This study was designed to define the factors involved in the variable acidification capacity of goat milk by lactic starters. Acidification capacity and compositional parameters of 28 goat milk samples were determined. The influences of the period of production and of some technological treatments (cold storage and heating) were also investigated. The results point out the influence of milk composition, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…On the other hand, in the region of Bouhanek, we recorded a low fat value of about 3.96% (Table 5); this low milk fat content may be due to the stage of lactation. (Masle and Morgan, 2001). Similar values to our fat study are reported by Drackova et al, (2008) with 5.6%.…”
Section: Qualitative Traitssupporting
confidence: 92%
“…On the other hand, in the region of Bouhanek, we recorded a low fat value of about 3.96% (Table 5); this low milk fat content may be due to the stage of lactation. (Masle and Morgan, 2001). Similar values to our fat study are reported by Drackova et al, (2008) with 5.6%.…”
Section: Qualitative Traitssupporting
confidence: 92%
“…A high proportion of proteins and minerals promotes the activity of lactic acid bacteria. Data presented by Masle and Morgan [ 41 ] also showed that the composition of goat milk depends on the lactation stage; therefore, the susceptibility of goat milk to acidification varies with the lactation stage.…”
Section: Resultsmentioning
confidence: 99%